Association of pruritus and chronic cough: an all of us database study - Divija Sharma; Juliana Pulsinelli; Joel Correa da Rosa; Zhen Wang; Brian Kim; Benjamin Ungar (Taylor & Francis Group, 2024)
AbstractPurpose Based on a potential shared pathophysiology tied to mast cell activity and neurogenic inflammation that may link pruritus and chronic cough (CC), this study, leveraging the All of Us database, examines the association between the two conditions.Materials and methods A nested case-control comparison was used to examine the association, identifying cases with SNOMED codes 418363000 (pruritus) and 68154008 (CC). Matching was performed on a 1:4 ratio by age, sex, and ethnicity using the MatchIt package in R, followed by maximum likelihood method to estimate odds ratios (ORs) and 95% confidence intervals from 2x2 contingency tables.Results CC patients (n = 2,388) were more than twice as likely to be diagnosed with pruritus (OR: 2.65) and pruritus patients (n = 22,496) were more than twice as likely to be diagnosed with CC (OR: 2.57), than respective matched controls.Conclusions These results highlight the potential bidirectional relationship between CC and pruritus, suggesting possible shared immune and neural pathways. Treatments like difelikefalin and nalbuphine that modulate these pathways, alongside P2X3 targeting agents, are emerging as potential therapeutic approaches for itch and chronic cough given the possible interconnected pathophysiology. This study's insights into the associations between pruritus and CC may pave the way for targeted therapeutic strategies that address their shared mechanisms.